Task-Related c-Fos Expression in the Posterior Parietal Cortex During the “Rubber Tail Task” Is Diminished in Ca2+-Dependent Activator Protein for Secretion 2 (Caps2)-Knockout Mice - Wada, Makoto; Takano, Kouji; Ide, Masakazu; Sano, Yoshitake; Shinoda, Yo; Furuichi, Teiichi; Kansaku, Kenji (Frontiers in Behavioral Neuroscience, 2021)
Rubber hand illusion (RHI), a kind of body ownership illusion, is sometimes atypical in individuals with autism spectrum disorder; however, the brain regions associated with the illusion are still unclear. We previously reported that mice responded as if their own tails were being touched when rubber tails were grasped following synchronous stroking to rubber tails and their tails (a “rubber tail illusion”, RTI), which is a task based on the human RHI; furthermore, we reported that the RTI response was diminished in Ca2+-dependent activator protein for secretion 2-knockout (Caps2-KO) mice that exhibit autistic-like phenotypes. Importance of the posterior parietal cortex in the formation of illusory perception has previously been reported in human imaging studies. However, the local neural circuits and cell properties associated with this process are not clear. Therefore, we aimed to elucidate the neural basis of the RTI response and its impairment by investigating the c-Fos expression in both wild-type (WT) and Caps2-KO mice during the task since the c-Fos expression occurred soon after the neural activation. Immediately following the delivery of the synchronous stroking to both rubber tails and actual tails, the mice were perfused. Subsequently, whole brains were cryo-sectioned, and each section was immunostained with anti-c-Fos antibody; finally, c-Fos positive cell densities among the groups were compared. The c-Fos expression in the posterior parietal cortex was significantly lower in the Caps2-KO mice than in the WT mice. Additionally, we compared the c-Fos expression in the WT mice between synchronous and asynchronous conditions and found that the c-Fos-positive cell densities were significantly higher in the claustrum and primary somatosensory cortex of the WT mice exposed to the synchronous condition than those exposed to the asynchronous condition. Hence, the results suggest that decreased c-Fos expression in the posterior parietal cortex may be related to impaired multisensory integrations in Caps2-KO mice.